STATUS ENTOMOLOGI NYAMUK Aedes aegypti DI DAERAH RAWAN DEMAM BERDARAH DENGUE KELURAHAN BENTENGNGE KABUPATEN PINRANG SULAWESI SELATAN - , Muhammad Sabir ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Dengue Haemorrhagic Fever (DHF) is an important health problem in Indonesia including Bentengnge Village, Pinrang District, South Sulawesi, Indonesia. Dengue viruses survive in nature by two mechanisms